Soft Skills & Metacognition as Inclusion Amplifiers in the 21st Century - Mitsea, Eleni; Drigas, Athanasios; Mantas, Panagiotis (International Journal of Online and Biomedical Engineering (iJOE), 2021)
In the present paper we investigate soft skills in the light of metacognition. We seek the essential soft skills in the 21st century including green skills and look into their cognitive and metacognitive background. Enlightening the soft skills’ dependence on metacognition, we conclude on a metacognition-based approach and suggest useful tools and strategies. The metacognitive approach of soft skills can be applied in a variety of educational contexts as a training paradigm to accelerate the inclusion and success of students, employees and citizens, especially those belonging in vulnerable groups like persons with disabilities.